2017
DOI: 10.3389/fpsyg.2017.00577
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Validity of the Structured Assessment of Violence Risk in Youth for Young Spanish Offenders

Abstract: The present study examined the predictive validity of the Structured Assessment of Violence Risk in Youth (SAVRY) in a group of young Spanish offenders. The sample is made up of 594 minors from the Juvenile Court, between the ages of 14 and 18 at the time they committed the delinquent act. The SAVRY was able to differentiate between low and high-risk younger offenders. Mean scores on risk factor are greater in the group of recidivist offenders, the group of non-recidivist shows higher mean scores in Protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
6
0
1
Order By: Relevance
“…El principal instrumento utilizado en esta investigación fue la Evaluación estructurada del riesgo de violencia en la juventud (SAVRY) (Borum et al, 2003) con la adaptación española de Vallés y Hilterman (2006). Esta es una herramienta que predice la reincidencia delictiva usando 30 variables, de las que 24 son de riesgo y seis de protección; además, presenta amplia réplica por la comunidad científica (Lodewijks et al, 2008;Navarro-Pérez y Pastor, 2017;Shepherd et al, 2014;Ortega-Campos et al, 2017), en especial cuando se trata de adolescentes privados de la libertad, como en este estudio (Gammelgard et al, 2008;Klein et al 2012).…”
Section: Instrumentosunclassified
“…El principal instrumento utilizado en esta investigación fue la Evaluación estructurada del riesgo de violencia en la juventud (SAVRY) (Borum et al, 2003) con la adaptación española de Vallés y Hilterman (2006). Esta es una herramienta que predice la reincidencia delictiva usando 30 variables, de las que 24 son de riesgo y seis de protección; además, presenta amplia réplica por la comunidad científica (Lodewijks et al, 2008;Navarro-Pérez y Pastor, 2017;Shepherd et al, 2014;Ortega-Campos et al, 2017), en especial cuando se trata de adolescentes privados de la libertad, como en este estudio (Gammelgard et al, 2008;Klein et al 2012).…”
Section: Instrumentosunclassified
“…A number of studies have investigated the predictive validity of the SAVRY protective factors. Many of these studies have indicated that SAVRY protective factors are associated with reduced likelihood of reoffending (i.e., Gammelgård, Koivisto, Eronen, & Kaltiala-Heino, 2015; Guy, 2008; Lodewijks, de Ruiter, & Doreleijers, 2010; McGowan, Horn, & Mellott, 2011; Ortega-Campos, García-García, & Zaldívar-Basurto, 2017; Rennie & Dolan, 2010; Schmidt, Campbell, & Houlding, 2011; Shepherd, Luebbers, Ogloff, Fullam, & Dolan, 2014; Vincent, Guy, Gershenson, & McCabe, 2012). However, other studies have failed to find significant associations (i.e., Hilterman, Nicholls, & van Nieuwenhuizen, 2014; Klein, Rettenberger, Yoon, Köhler, & Briken, 2015; Penney, Lee, & Moretti, 2010; Perrault, Vincent, & Guy, 2017; Viljoen et al, 2008), or have yielded mixed results (i.e., Chu, Goh, & Chong, 2016; Dolan & Rennie, 2008; Vincent, Chapman, & Cook, 2011; Zhou, Witt, Cao, Chen, & Wang, 2017).…”
Section: Measurement Of Protective Factors In Adolescent Risk Assessmmentioning
confidence: 99%
“…There are relevant legal and cultural differences between the Spanish and Anglo-Saxon cultures that may affect the validity of the YLS/CMI, such as the different legal systems and the collectivism versus individualism cultural differences. For instance, according to the Spanish legal system, minors between 14 and 17 years old can be judged under the juvenile system, and subsequently assigned a wide range of educational measures (Cuervo & Villanueva, 2015; Ortega-Campos et al, 2017). Educational measures are sanctions received by youth according to their risk level.…”
Section: Introductionmentioning
confidence: 99%